Survey on Access Control Mechanisms in Cloud Computing - AKBULUT, AKHAN; BAYDOĞMUŞ, GÖZDE KARATAŞ (River Publishers, 2018)
The benefits that Internet-based applications and services have given to the end user with today’s cloud computing technology are very remarkable. The distributed services instantly scaled over the Internet provided by cloud computing can be achieved by using some mechanisms in the background. It is a critical task for end users to control access to resources because lack of control often leads to security risks. In addition, this may cause systems to fail. This paper describes seven different access control mechanisms used in cloud computing platforms for different purposes. Besides, the advantages and disadvantages of various models developed from previous service-based architectures and used for cloud computing are detailed and classified. During the assessments, NIST’s metrics were taken as a reference, and in the study, 109 articles from the past decade were examined. We also compared our research with the existing survey papers.
Keywords: Cloud Computing; Information Policy Making; Access Control; Security; NIST Metrics